Computerized posturography is more sensitive than clinical Romberg Test in detecting postural control impairment in minimally impaired Multiple Sclerosis patients - Melillo, Federica; Di Sapio, Alessia; Martire, Serena; Malentacchi, Maria; Matta, Manuela; Bertolotto, Antonio (Multiple sclerosis and related disorders, 2017)
Balance impairment, frequent in Multiple Sclerosis patients (MS), is difficult to detect promptly with routine clinical examination. Computerized platforms can measure subtle deficit but, given the complexity of postural system, multiple tests should be adopted. To evaluate whether platform was more sensitive than Romberg Test (RT) in detecting balance abnormalities, we 1) chose a battery of posturographic tests, 2) collected normative data from 58 healthy subjects 3) applied the tests to Clinically Isolated Syndrome (n=42) and minimally impaired MS (n=76). Subjects underwent 3 trials of quiet standing with eyes open and closed (modified Clinical Test of Sensory Interaction on Balance, mCTSIB) and 4 trials of voluntary anterior and lateral maximal leaning on right and left sides (Limits of Stability, LOS), giving 10 postural indexes. For every subject, the best trials were selected for subsequent analysis. Normative values were established in a range from 1st to 99th percentile, defining balance impairment by the presence of at least 2 indexes out of range. Even adopting the above mentioned strict definition of balance impairment, the forceplate resulted more sensitive than RT, detecting abnormalities in 25% of patients, while RT was abnormal in 7% only. In RT-negative patients with 1-year follow-up (n =67) the detection of a single abnormal index was able to predict a subsequent onset of symptomatic balance impairment. The proposed procedure is quick, easy to perform and can improve the assessment of the clinical course of MS, from a pre-clinical stage up to medium degree of disability. •The proposed posturographic test protocol is quick and easy to perform.•The posturographic tests clearly differentiate patients from healthy subjects.•Positive Romberg Test (RT) is associated with a greater number of abnormal indexes.•The posturographic tests proved to be more sensitive than RT.•The presence of at least one abnormal index predicts a positive RT at one year.